Design screening and analysis of gas-fired ammonia-based chemisorption heat pumps for space heating in cold climate. (15th September 2020) - Yang, Zhiyao; Qu, Ming; Gluesenkamp, Kyle R.
Abstract: Thermally-driven ammonia-based chemisorption heat pumps (CSHP) have the potential to provide high-efficiency space heating in cold climates. Using the reversible chemical bond between sorbent salt and ammonia, CSHP thermochemically pumps heat from the cold ambient to the end-uses of space heating at 50 °C. The heating coefficient of performance (COP) of a CSHP is largely dependent on the selection of the sorbent salts, cycle configuration, and the system operation. This study uses a thermodynamic model to investigate the performance of six CSHP system configurations, including four single-effect and two double-effect cycles. The feasibility and performance of 121 available NH3 /salt reactions are studied for each configuration. The thermal COP of the cycles and the primary energy COP of the gas-fired CSHP systems are evaluated assuming 50 °C supply temperature for building space heating and the optimal system designs are identified. The highest thermal COP for single-effect and double-effect cycles under −25 °C ambient temperatures are predicted to be 1.22 and 1.57, respectively. The corresponding primary energy COPs are above 1.0 and 1.15, which are 30% higher than condensing furnaces and is sustained into the same cold temperatures. Highlights: Introduced a method to screen chemisorption reactions for cold-climate heating. Screened 121 NH3 /salt reactions for optimal COP in 6 cycle configurations. Double-effect cycles can reach cycle COP >1.5 under > -29 °C ambient. CSHP can reach 30% higher primary COP than conventional heating technologies.